Crystal structures of the extracellular domain from PepT1 and PepT2 provide novel insights into mammalian pPeptide transport - Beale, John H.; Parker, Joanne L.; Samsudin, Firdaus; Barrett, Anne L.; Senan, Anish; Bird, Louise E.; Scott, David; Owens, Raymond J.; Sansom, Mark S.P.; Tucker, Stephen J.; Meredith, David; Fowler, Philip W.; et al. (Elsevier, 2015)
Mammals obtain nitrogen via the uptake of di- and tri-peptides in the gastrointestinal tract through the action of PepT1 and PepT2, which are members of the POT family of proton-coupled oligopeptide transporters. PepT1 and PepT2 also play an important role in drug transport in the human body. Recent crystal structures of bacterial homologs revealed a conserved peptide-binding site and mechanism of transport. However, a key structural difference exists between bacterial and mammalian homologs with only the latter containing a large extracellular domain, the function of which is currently unknown. Here, we present the crystal structure of the extracellular domain from both PepT1 and PepT2 that reveal two immunoglobulin-like folds connected in tandem, providing structural insight into mammalian peptide transport. Functional and biophysical studies demonstrate that these domains interact with the intestinal protease trypsin, suggesting a role in clustering proteolytic activity to the site of peptide transport in eukaryotic cells.